The Sopranos : born under a bad sign - Ricci, Franco, 1953- (Toronto Italian studies., 2014)
In The Sopranos: Born under a Bad Sign, Franco Ricci presents an insightful analysis of the groundbreaking HBO series and its complex psychological themes.